Purwarupa Sistem Kendali Kestabilan Pesawat Tanpa Awak Sayap Tetap Menggunakan Robust PID - Dwitiya Bagus Widyantara; Raden Sumiharto; Setyawan Bekti Wibowo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
This study has implemented stability control system of Unmanned Aerial Vehicle (UAV) using robust PID. The aircraft stability refers to wind against in glidding condition with straight movement. Robust PID used to control aircraft motion system. Control parameters obtained from the IMU sensor roll, pitch and yaw. IMU data are computed using DCM algorithm that produces Eulerian angles. Type PID control is determined by Ziegler-Nichols methods theory of oscillations. Control system are varied three types, there are P, PI, and PID. The results have the best type of PID control with D constant value = 0 for each motion systems. PID constant value used for the aileron Kp = 2,93, Ki = 2,808 and Kd = 0, elevators Kp = 2,02, Ki = 1,731 and Kd = 0 and rudder Kp = 1,35, Ki = 0,9 and Kd = 0. Robust method using ISE (Integral Squared Error) which replaces integral PID control error. The system was tested using two mode. Mode A (Manual-PID-RobustPID) and mode B (Manual-RobustPID-PID). The result of robust PID methods is able to make the system response to disturbances better than regular PID that increase the settling time of aileron 63.67% , elevator 41.42% and rudder 57.33%.